Effect of ion bombardment on the chemical properties of crystalline tantalum pentoxide films - Perez, Israel (2019)
The effect of argon ion bombardment on the chemical properties of crystalline Ta2O5 films grown on Si(100) substrates by radio frequency magnetron sputtering was investigated by X-ray photoelectron spectroscopy. All samples were irradiated for several time intervals [(0.5, 3, 6, 9) min] and the Ta 4f and O 1s core levels were measured each time. Upon analysis at the surface of the films, we observe the Ta 4f spectrum characteristic of Ta2O5. Irradiated samples exhibit the formation of Ta suboxides with oxidation states Ta1+, Ta2+, Ta3+ Ta4+, and Ta5+. Exposing the films, after ion bombardment, to ambient for some days stimulates the amorphous phase of Ta2O5 at the surface suggesting that the suboxides of Ta are unstable. Using a sputtering simulation we discuss that these suboxides are largely generated during ion bombardment that greatly reduces the oxygen to tantalum ratio as the irradiation time increases. The computer simulation indicates that this is due to the high sputtering yield of oxygen.